Legal implications of emerging technologies in criminal investigations: current challenges and catalysts for change - Elshobake, Mohammed R. M.; Sakka, Alaa (Macrothink Institute, 2024)
This paper focuses on the transformative impact of developing technology on criminal investigations, as well as the legal repercussions. The research reveals the multifaceted obstacles and opportunities that these innovations provide within the criminal justice framework, such as artificial intelligence. The research examines the developing balance between police enforcement activities and individual rights by examining some current cases and legal precedents, addressing problems of privacy, due process, and evidence standards. This research will employ the descriptive-analytical method and case study approach to conduct a comprehensive examination of the Legal Implications of Emerging Technologies in Criminal Investigations. The article suggests adaptive strategies to provide a nuanced approach that supports rapid technology innovation by identifying holes in existing legal systems. The research provides critical insights to policymakers, legal practitioners, and scholars navigating the dynamic convergence of law and technology, providing a complete grasp of the change agents in the ever-changing landscape of criminal investigations.